Pengaruh Penerapan Sistem Informasi Akuntansi dan Pemanfaatan Teknologi Informasi Terhadap Kinerja Operasional UMKM - Selfina Erawati; Fenny Afrida; Johnny Chandra; Anton Eka Saputra; Fery Wahyudi (Jurnal Minfo Polgan, 2026)
This study aims to analyze the effect of accounting information systems and the utilization of information technology, both simultaneously and partially, on the operational performance of mobile coffee shop MSMEs in Medan. This research employs a quantitative approach using primary data collected through questionnaires distributed to 65 respondents who are mobile coffee shop MSME actors in Medan, selected using purposive sampling. The data analysis method used is multiple linear regression with the model: Operational performance = 2.041 + 0.493 Accounting Information Systems + 0.807 Utilization of Information Technology + e. The results show that partially, accounting information systems have a positive and significant effect on operational performance, as indicated by a significance value of < 0.05 and a t-value greater than the t-table, and the utilization of information technology also has a positive and significant effect on operational performance with a significance value of < 0.05 and a t-value greater than the t-table. Simultaneously, both variables have a significant effect on operational performance, as evidenced by an F-value of 1617.899 with a significance level of < 0.05. The coefficient of determination (R²) of 0.981 indicates that 98.1% of the variation in operational performance can be explained by these variables, while the remaining 1.9% is influenced by other factors outside the research model.